Statins Attenuate Helicobacter pylori CagA Translocation and Reduce Incidence of Gastric Cancer: In Vitro and Population-Based Case-Control Studies. - Chun-Jung Lin (PLoS ONE, 2016)
Gastric cancer is the second leading cause of cancer-related death worldwide. The correlation of Helicobacter pylori and the etiology of gastric cancer was substantially certain. Cholesterol-rich microdomains (also called lipid rafts), which provide platforms for signaling, are associated with H. pylori-induced pathogenesis leading to gastric cancer. Patients who have been prescribed statins, inhibitors of 3-hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase, have exhibited a reduced risk of several types of cancer. However, no studies have addressed the effect of statins on H. pylori-associated gastric cancer from the antineoplastic perspective. In this study, we showed that treatment of gastric epithelial cells with simvastatin reduced the level of cellular cholesterol and led to attenuation of translocation and phosphorylation of H. pylori cytotoxin-associated gene A (CagA), which is recognized as a major determinant of gastric cancer development. Additionally, a nationwide case-control study based on data from the Taiwanese National Health Insurance Research Database (NHIRD) was conducted. A population-based case-control study revealed that patients who used simvastatin exhibited a significantly reduced risk of gastric cancer (adjusted odds ratio (OR) = 0.76, 95% confidence interval (CI) = 0.70-0.83). In patients exhibiting H. pylori infection who were prescribed simvastatin, the adjusted OR for gastric cancer was 0.25 (95% CI = 0.12-0.50). Our results combined an in vitro study with a nationwide population analysis reveal that statin use might be a feasible approach to prevent H. pylori-associated gastric cancer.